Cerebellar gray matter differentiates children with early language delay in autism. Issue 11 (22nd March 2016) - D'Mello, Anila M.; Moore, Dorothea M.; Crocetti, Deana; Mostofsky, Stewart H.; Stoodley, Catherine J.
Abstract : Early language delay (ELD) is one of the earliest indicators of autism spectrum disorder (ASD), and predicts later cognitive and behavioral outcomes. We aimed to determine the neural correlates of ELD in autism, and examine the relationships between gray matter (GM), age of first word/phrase, and core ASD symptoms. We used voxel‐based morphometry to examine whole‐brain differences in GM in 8–13 year old children with autism ( n  = 13 ELD; n  = 22 non‐ELD) and 35 age‐matched typically developing (TD) children. Multiple regression analyses examined the relationships between GM, age of first word/phrase, and autism diagnostic observation schedule (ADOS) scores. Composite age of first word/phrase negatively correlated with GM throughout the cerebellum. Both ASD groups (ELD and non‐ELD) had reduced GM in right cerebellar Crus I/II when compared to TD children. Left cerebellar Crus I/II was the only region in the brain that differentiated ELD and non‐ELD children, with ELD children showing reduced GM relative to both non‐ELD and TD groups. Group×score interactions converged in left Crus I/II, such that the non‐ELD group showed poorer ADOS scores with increasing GM, whereas the ELD group showed poorer ADOS scores as GM decreased. Reduced GM in right cerebellar Crus I/I was related ASD diagnosis, while children with ELD showed additional reduced GM in left Crus I/II. These findings highlight the importance of specific cerebellar networks in both ASD and early language development, and suggest that bilateral disruption in cerebellar regions that interconnect with fronto‐parietal networks could impact language acquisition in ASD. Autism Res 2016, 9: 1191–1204 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.